Relationship of BMI and rs12255372 TCF7L2 Polymorphism on the Conversion to Type 2 Diabetes Mellitus in Lactating Women with Previous Gestational Diabetes - Ruth Reyes-López; Elva Perez-Luque; Juan Manuel Malacara (Medical Science: Trends and Innovations Vol. 13, 2025)
Women with previous gestational diabetes mellitus (pGDM) have a high risk of developing postpartum type 2 diabetes mellitus (T2DM). Several reports have shown that approximately 50% of women with GDM will develop diabetes within 5 years. There are other risk factors for postpartum diabetes as a family history of diabetes, pre-pregnancy and postpartum body mass index, dietary patterns, physical activity, and breastfeeding. This study aimed to analyse the relationship between BMI and rs12255372 TCF7L2 polymorphisms in the conversion to T2DM in lactating women with pGDM. One hundred and fifty-three women con pGDM were recruited from public hospitals of León, Guanajuato, México. Three groups: normal glucose tolerance (NGT), impaired glucose tolerance (IGT), and T2DM after the oral glucose tolerance test were formed. All women were interviewed and asked about their glycemic control and the time since their last glucose test. Serum glucose concentrations and lipid profiles were measured using enzymatic methods with an analyser. Metabolic and hormone variables were measured, and genotyping was performed. The questionnaire included data on lactation (yes/no), duration of lactation, and full lactation. After 35 (21–49) months from the last partum, 54% of women had an NGT, 30.7% IGT, and 15% T2DM. BMI and rs12255372 are associated with the risk of conversion to IGT and T2DM [OR = 1.07 (95% IC 1.0–1.14, p = 0 .041; OR = 2.14, 95% IC 1.01–4.55, p = 0 .04 respectively), while the lactation shows a strong protective effects OR = 0.15 (95% IC 0.062–0.39, p = 0.00007), and an apparent interaction with rs12255372T decreasing the risk in carriers (OR = 2.15; 95% IC 0.97–4.7, p = 0 .05). BMI is an independent risk factor of IGT/T2DM development. Both sporadic and long-term breastfeeding are associated with a lower risk of T2DM and a better metabolic profile in women with a history of GDM. The multivariate analysis revealed that both BMI and the rs12255372 predicted the conversion to IGT and T2DM in women with pGDM. The lactation shows a strong protective effect and a possible interaction with rs12255372 polymorphism. In conclusion, it means that lactation and polymorphism share variability by means of an interaction of an unidentified nature. Further studies are necessary to confirm a possible interaction of rs12255372 TCF7L2 with full breastfeeding and lactation duration.